Role of central neurophysiological systems in placebo analgesia and their relationships with cognitive processes mediating placebo responding. (May 2011) - Brown, Christopher; Watson, Alison; Morton, Debbie; Power, Andrea; El-Deredy, Wael; Jones, Anthony
The harnessing of the positive aspects of the placebo effect in clinical practice is a major clinical and ethical challenge, and requires better understanding of placebo mechanisms. In this article, we present an explanatory cognitive model of placebo analgesia, centered on expectation of pain relief, and present direct and indirect evidence for the psychological and physiological drivers and downstream mediators of the effects of expectation on reduction in pain. The endogenous opioid system is involved in expectation-mediated analgesia, but it is not known whether this system is required for the generation or downstream effects of expectation. There is indirect evidence to support the role of other neurotransmitter systems, such as the serotonergic and dopamine systems, and a possible role of the hypothalamic––pituitary––adrenal stress axis. The future challenge is the identification of the causal role of these systems in placebo analgesia, which would provide an empirical basis for exploring new pain therapies.